2015
DOI: 10.3109/13880209.2015.1005751
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and pharmacological properties of the essential oils obtained seasonally fromLippia thymoides

Abstract: Submit your article to this journal Conclusions: Lippia thymoides is a source of natural products of pharmaceutical interest, being necessary additional studies to determine the substances involved in the biological activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 47 publications
1
16
0
4
Order By: Relevance
“…The yield of dried leaves of L . thymoides from state of Bahia (Brazil) showed seasonal variation, and its values varied between 2.14% and 2.93% [39].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The yield of dried leaves of L . thymoides from state of Bahia (Brazil) showed seasonal variation, and its values varied between 2.14% and 2.93% [39].…”
Section: Resultsmentioning
confidence: 99%
“…Silva et al [39]reported that the essential oil from the leaves of a specimen of L . thymoides contains sesquiterpeneβ-caryophyllene (17.22–26.27%) as the main component, followed by borneol (4.45–7.36%), camphor (3.22–8.61%), camphene (2.64–5.66%), and germacrene-D (4.72–6.18%).…”
Section: Resultsmentioning
confidence: 99%
“…Male (250-300 g) Wistar rats were used in the assays and kept as described in the Supplementary Material. Isolated rat aortae were prepared as previously described (Silva et al 2016). Briefly, preparations were made in the presence or absence of the functional endothelium.…”
Section: Methodsmentioning
confidence: 99%
“…It is popularly known as "alecrim-do-mato" or "alecrim-do-campo," and it is used in religious rituals and folk medicine to treat wounds, fever, bronchitis, rheumatism, headache, and weakness (Almeida and Bandeira 2010;Funch et al 2004). Previously, our research group showed that volatile oils from L. thymoides have β-caryophyllene as the major component and possess spasmolytic activity in the rat aorta and uterus (Silva et al 2016). The leaf extract of this species has high contents of phenolic substances, and it reduces the rectal temperature of young rats with hyperthermia induced by yeast (Silva et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols from L. citriodora decreased triglyceride (TG) accumulation, the generation of reactive oxygen species (ROS) and restored mitochondrial membrane potential in adipocytes via ROS-mediated down-regulation of nuclear factor κB transcription factor, peroxisome proliferator-activated receptor γ-dependent transcription, upregulation of adiponectin and activation of AMP-activated protein kinase (AMPK) [2]. Essential oils from L. thymoides leaves had antimicrobial selectivity to Gram-positive bacteria Staphylococcus aureus and Micrococcus luteus [3]. Methanolic extract of L. nodiflora leaves showed reduced effect on ROS production against LPS induced toxicity in HepG2 cells [4].…”
Section: Introductionmentioning
confidence: 99%